Effect of equex on ram semen in different freezing extenders - Ebru ŞENGÜL; Cemal DAYANIKLI; Bilge ALPCAN KÜNYELİ; İsmail ÇOBAN; Bülent BÜLBÜL; Burcu ÜSTÜNER; Zekariya NUR (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2024)
This study was carried out to determine the effects of Equex on ram semen freezability in three different extenders. Semen samples were collected from five rams and divided into six equal aliquots. At first, three non-commercial base extenders (E1: Tris-based extender, E2: Tris based extender+ Cystein and E3: Skim Milk Powder (SMP)) were prepared. Each base extender was divided into two parts; a base extender (E1, E2 and E3) or fortified with Equex (E1E, E2E and E3E). The pooled semen was diluted according to the two-step dilution method, and cryopreserved using a programmable freezing machine. Sperm motility parameters were examined by CASA. The morphological properties were evaluated by flow cytometer. It was observed that the addition of Equex had a positive effect on post-thaw motility and live spermatozoa (P<0.001), but had no effect on the LIN and Polarized mitochondria. While the Equex addition decreased post-thaw VCL, VSL, VAP and WOB values, it didn"t have effect on the post-thaw intact acrosome rates (P<0.05). Furthermore, it was observed that Equex had a cryoprotective effect on post-thaw progressive motility in E1E and E3E groups (P<0.05), but was not observed in E2E group. In conclusion there was an interaction between Equex and extender ingredient. The cryoprotective effect of Equex was more evident in skim milkbased extender than that in tris-based extender.